Quality of Online Academic Services during the Covid-19 Pandemic at FKIP-UBT - Suprianto Suprianto; Sitti Hardiyanti Arhas; M. Awaluddin; Nisa Ariantini; M. Said Zainuddin (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The purpose of this study was to determine the quality of service in terms of quality, quantity, duration and need for supervision. This type of research is a combination research (mixed methods), which combines the types of quantitative and qualitative research. In order to obtain quantitative results, the population in this study was 59, so this research is a population study. Meanwhile, to obtain qualitative results, the selected informants were 5 people consisting of 2 lecturers and 3 students. Data collection techniques used are questionnaires, observations and interviews. The mixed methods research design used is a triangulation design. The results showed that the quality of academic services during the Covid-19 pandemic at FKIP UBT was in the good category.